ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMAKAIAN KONDOM DAN PELICIN PADA LELAKI SEKS LELAKI (LSL) SEBAGAI UPAYA PENCEGAHAN HIV (STUDI KUANTITATIF PADA SEMARANG GAYA COMMUNITY) - Putri Ade Chandra; Zahroh Shaluhiyah; Kusyogo Cahyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Semarang is considered metropolitan city included in 5 top city/district with the largest number of population in Central Java along with the largest number of HIV and AIDS case accumulated since 1993 to September 2014 with amount of 1409 cases. Number of cases accumulated since the past 8 years shows 7% among the cases are MSM, as it is also ranked second for the cause of AIDS following heterosexual as risk factor. Condom and lubricant consistent use during sex can be done as HIV and AIDS dissemination prevention. This study aims to analyze the factors that are related to consistent condom and lubricant use among MSM. The method of this study was cross sectional with 96 samples collected with purposive sampling. Chi square was used to analyze the association in ordinal and nominal data this study shows 63.5% samples use condom and lubricant consistently during sex. The factors that associated with consistent condom and lubricant use are perceived susceptibility of being infected to HIV and AIDS (p=0.002)¸ perceived severity in HIV infection (p=0.002), perceived benefit of condom and lubricant use (p=0.001), perceived barrier in condom and lubricant use (p=0.003), cues to consistent condom and lubricant use (p=0.020) and history of STD infection (p=0.005). Meanwhile, demographic status like education level (p=0.319), vocation (p= 0.665), marriage status (p=0.479), and age (p=0.691) also knowledge about HIV, AIDS, condom and lubricant (p= 0.099) are not associated with consistent use of condom and lubricant during sex among MSM